Anode for all-solid-state battery, all-solid-state battery, and anode active material for all-solid-state battery
By using high rebound carbon materials and sulfide solid electrolytes in all-solid-state batteries, the composition and structure of the negative electrode materials are optimized, and the shortcomings of the negative electrode living substances in carbon material in terms of cycle characteristics and primary charge and discharge efficiency are solved, and the battery performance is significantly improved.
Patent Information
- Application Number
- JP2022571576
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-24
- Filing Date
- 2021-12-22
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-12-22
AI Technical Summary
The carbon material negative electrode living substances in existing all-solid state batteries have shortcomings in terms of cycle characteristics and primary charge and discharge efficiency, which affects the overall performance of the battery.
Carbon material with a rebound rate of 13% or higher is used as the negative electrode living, and the surface spacing is determined to be between 0.336 nm and 0.350 nm in XRD measurement, and the composition and structure of the negative electrode material are optimized in combination with the sulfide solid electrolyte.
It significantly improves the cycle characteristics and initial charging and discharging efficiency of all solid state batteries, extends the service life of the battery and improves the overall performance.
Smart Images

Figure 0007666523000003 
Figure 0007666523000001 
Figure 0007666523000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a negative electrode for an all-solid-state battery, an all-solid-state battery, and a negative electrode active material for an all-solid-state battery. [Background technology]
[0002] 2. Description of the Related Art Rechargeable lithium-ion secondary batteries are widely used as power sources for various electronic devices. In recent years, the use of lithium-ion secondary batteries as power sources for automobiles such as electric vehicles and hybrid vehicles has also been considered.
[0003] Many of the lithium-ion secondary batteries currently on the market use a liquid electrolyte in which the electrolyte is dissolved in a flammable organic solvent. For this reason, it is necessary to take measures such as providing a safety device to suppress temperature rise in the event of a short circuit. For this reason, secondary batteries in which the electrolyte is in a solid state (all-solid-state batteries) have been proposed. All-solid-state batteries are superior in terms of safety in the event of a short circuit compared to batteries that use an electrolyte containing an organic solvent. For this reason, it is thought that the safety device can be simplified, and the manufacturing cost and productivity of secondary batteries will be excellent.
[0004] An all-solid-state battery is mainly composed of a positive electrode containing a positive electrode active material, a solid electrolyte layer, and a negative electrode containing a negative electrode active material. Although lithium titanate (LTO) is the mainstream negative electrode active material for all-solid-state batteries, the use of carbon materials such as graphite is also being considered (see, for example, JP 2018-206487 A). Summary of the Invention [Problem to be solved by the invention]
[0005] Carbon materials are promising as negative electrode active materials for all-solid-state batteries from the viewpoints of increasing battery capacity and reducing costs, but there is room for improvement in cycle characteristics (the rate at which battery capacity is maintained when repeatedly charged and discharged). In addition, from the viewpoint of increasing battery capacity, improvement of the initial charge / discharge efficiency is also desired.
[0006] In view of the above circumstances, an object of the present disclosure is to provide a negative electrode for an all-solid-state battery that enables production of an all-solid-state battery having excellent cycle characteristics and initial charge / discharge efficiency, an all-solid-state battery including this negative electrode, and a negative electrode active material for use in this all-solid-state battery. [Means for solving the problem]
[0007] Means for solving the above problems include the following embodiments. <1> The negative electrode active material includes a solid electrolyte, and the negative electrode active material has a lattice spacing (d 002 ) is 0.336 nm or more and less than 0.350 nm and a springback rate is 13% or more. <2> The carbon material is particles having a volume average particle size of 5 μm to 30 μm. <1> The negative electrode for an all-solid-state battery according to claim 1. <3> The BET specific surface area based on the nitrogen adsorption capacity of the carbon material is 0.5 m 2 / g~10m 2 / g, <1> or <2> The negative electrode for an all-solid-state battery according to claim 1. <4> a mass ratio of the negative electrode active material to the solid electrolyte (negative electrode active material:solid electrolyte) contained in the all-solid-state battery negative electrode is 5:95 to 70:30; <1> ~ <3> 13. The negative electrode for an all-solid-state battery according to claim 12. <5> The solid electrolyte is a sulfide solid electrolyte. <1> ~ <4> 13. The negative electrode for an all-solid-state battery according to claim 12. <6> <1> ~ <5> 13. An all-solid-state battery comprising: the negative electrode for an all-solid-state battery according to claim 12; a positive electrode; and a solid electrolyte layer disposed between the negative electrode for an all-solid-state battery and the positive electrode. <7> Interplanar spacing (d 002 ) is 0.336 nm or more and less than 0.350 nm and has a springback rate of 13% or more. Effect of the Invention
[0008] According to the present disclosure, there are provided a negative electrode for an all-solid-state battery capable of producing an all-solid-state battery having excellent cycle characteristics and initial charge / discharge efficiency, an all-solid-state battery including this negative electrode, and a negative electrode active material for use in this all-solid-state battery. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a cross-sectional view illustrating a schematic example of a configuration of an all-solid-state battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, the embodiments for carrying out the present disclosure will be described in detail. However, the present disclosure is not limited to the following embodiments. In the following embodiments, the components (including element steps, etc.) are not essential unless otherwise specified. The same applies to the numerical values and their ranges, and do not limit the present disclosure.
[0011] In the present disclosure, the term "step" includes not only a step that is independent of other steps, but also a step that cannot be clearly distinguished from other steps as long as the purpose of the step is achieved. In the present disclosure, a numerical range indicated using "~" includes the numerical values before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples. In the present disclosure, each component may contain multiple types of the corresponding substance. When multiple substances corresponding to each component are present in the composition, the content or amount of each component means the total content or amount of the multiple substances present in the composition, unless otherwise specified. In the present disclosure, the particles corresponding to each component may include multiple types. When multiple types of particles corresponding to each component are present in the composition, the particle size of each component means the value for a mixture of the multiple types of particles present in the composition, unless otherwise specified. In this disclosure, the term "layer" includes cases where the layer is formed over the entire area when the area in which the layer exists is observed, as well as cases where the layer is formed over only a portion of the area.
[0012] <Negative electrode for all-solid-state batteries> The negative electrode for an all-solid-state battery (hereinafter, also simply referred to as a negative electrode) of the present disclosure includes a negative electrode active material and a solid electrolyte, and the negative electrode active material has a lattice spacing (d 002 ) is 0.336 nm or more and less than 0.350 nm and the springback rate is 13% or more.
[0013] The all-solid-state battery using the above-mentioned negative electrode has superior cycle characteristics to conventional all-solid-state batteries using a carbon material as the negative electrode active material. The reason for this is not entirely clear, but is thought to be as follows. An all-solid-state battery is mainly composed of a positive electrode containing a positive electrode active material, a layer containing a solid electrolyte (hereinafter also referred to as a solid electrolyte layer), and a negative electrode containing a negative electrode active material. Furthermore, in order to promote the conduction of ions to the negative electrode, the negative electrode also contains a solid electrolyte, and the solid electrolyte and the negative electrode active material are in contact with each other within the negative electrode.
[0014] It is known that carbon materials undergo large volumetric changes accompanying the absorption and release of ions, and therefore, in an all-solid-state battery using a carbon material as the negative electrode active material, repeated charging and discharging causes the volumetric changes of the carbon material to reduce the contact area with the solid electrolyte in the negative electrode, destroy particles, and the like, and the cycle characteristics tend to deteriorate.
[0015] In contrast, the carbon material used as the negative electrode active material in the present disclosure has a springback ratio of 13% or more. The springback rate of a carbon material is an index showing the degree to which the carbon material returns to its original state when a predetermined pressure is applied to the carbon material and then the pressure is released. The larger the springback rate, the easier it is to return to the original state from the compressed state.
[0016] It is believed that carbon materials with a springback rate of 13% or more are less likely to undergo irreversible deformation such as destruction of the particle structure than carbon materials with a springback rate of less than 13%. As a result, it is believed that the contact area between the carbon material and the solid electrolyte is sufficiently maintained even after repeated charging and discharging, and deterioration of cycle characteristics is suppressed.
[0017] In addition to the above, as a result of the investigations by the present inventors, the planar spacing (d 002 All-solid-state batteries using carbon materials with a lattice spacing (d 002 It was found that the initial charge / discharge efficiency was superior to that of all-solid-state batteries using carbon materials with a thickness of 0.350 nm or more. The reason for this is not entirely clear, but it is thought to be because the lithium ions inserted between the carbon layers are less likely to be released.
[0018] (Negative electrode active material) The negative electrode active material is characterized by the interplanar spacing (d 002 ) includes carbon materials having a molecular weight of 0.336 nm or more and less than 0.350 nm (hereinafter also referred to as specific carbon materials).
[0019] The interplanar spacing (d 002 ) is an index showing the degree of disorder in the crystal structure of a carbon material, and the interplanar spacing (d 002 Carbon materials with a lattice spacing (d 002 ) of 0.340 nm or more may be classified as non-graphite. Among non-graphite carbon materials, the interplanar spacing (d 002 Carbon materials with a lattice spacing (d 002) of 0.350 nm or more is sometimes classified as hard carbon (non-graphitizable carbon).
[0020] The interplanar spacing (d 002 ) is 0.336 nm or more in order to suppress the volume fluctuation caused by the absorption and release of lithium ions. 002 ) may be 0.339 nm or more, 0.340 nm or more, 0.342 nm or more, or 0.343 nm or more. The interplanar spacing (d 002 ) tends to reduce the volumetric fluctuations associated with the absorption and release of lithium ions. This is thought to result in less damage to the particles even with repeated charging and discharging, maintaining the contact area with the solid electrolyte, and more effectively suppressing the deterioration of cycle characteristics.
[0021] The interplanar spacing (d 002 ) is not particularly limited as long as it is in the range of 0.336 nm or more and less than 0.350 nm, and may be 0.349 nm or less, or may be 0.348 nm or less.
[0022] In the present disclosure, the lattice spacing (d 002 ) is measured as follows: To correct the diffraction peak positions, a sample is prepared by mixing silicon powder as an internal standard material in an agate mortar for 3 minutes so that the mass ratio of the carbon material and silicon powder (carbon material:silicon powder) is 3:2. The sample is then irradiated with X-rays under the following conditions, and the spectra of the diffraction peaks corresponding to the silicon (111) plane and the carbon (002) plane are measured. (Measurement conditions) ·Characteristic X-ray: CuKα ray Scan speed: 0.25° / min Divergence slit: 1° Scattering slit: 1° Receiving slit: 0.15mm
[0023] The measured diffraction angle corresponding to the (111) plane of silicon is θSi(111) , the diffraction angle corresponding to the (002) plane of carbon is θ C(002) From Bragg's equation (1), the interplanar spacing (d 002 ) is calculated. In equation (1), the theoretical diffraction angle corresponding to the (111) plane of silicon is θ Si-theoretical(111) = 14.221, where λ is the X-ray wavelength (0.15418 nm for CuKα radiation).
[0024]
number
[0025] The specific carbon material contained in the negative electrode has a lattice spacing (d 002 Even if only one type has the same interplanar spacing (d 002 ) may be a combination of two or more different types.
[0026] The springback rate of the carbon material is measured as follows. A cylindrical powder molding die (diameter 15.0 mm) is filled with 3.000 (±0.005) g of carbon material. The density of the carbon material filled in the die is determined to be 1.65 g / cm using an autograph. 3 Uniaxial pressure is applied until the density of the carbon material reaches 1.65 g / cm 3 After the pressure reaches 2N, the pressure is released to 0N and the state (0N state) is maintained for 30 seconds. After the 30 second hold, the sample is pressurized using an autograph, and the density ρ of the sample when the pressure reaches 2N is measured. after (g / cm 3 ) is measured. The springback rate is calculated from the obtained value using the following formula. Springback rate (%) = {(1.65-ρ after ) / 1.65}×100
[0027] From the viewpoint of cycle characteristics, the springback rate of the specific carbon material may be 14% or more, 15% or more, 17% or more, 18% or more, or 20% or more.
[0028] The upper limit of the springback rate of the specific carbon material is not particularly limited, but may be 65% or less, 60% or less, 50% or less, 40% or less, or 35% or less.
[0029] Methods for adjusting the springback rate of the carbon material include adjusting the graphitization degree, particle shape, particle size distribution, etc. of the carbon material, and reducing the pores of the carbon material.
[0030] The specific carbon material is preferably in a particulate form. The particulate specific carbon material may be in the form of ungranulated primary particles or granulated secondary particles.
[0031] When the specific carbon material is particulate, the volume average particle diameter is preferably 5 μm to 30 μm. When the volume average particle diameter of the specific carbon material is 5 μm or more, the initial charge / discharge efficiency tends to be improved, and when it is 30 μm or less, the input / output characteristics tend to be improved. The volume average particle diameter of the specific carbon material may be 8 μm or more, 10 μm or more, or 12 μm or more. The volume average particle diameter of the specific carbon material may be 28 μm or less, 26 μm or less, or 24 μm or less.
[0032] In the present disclosure, the volume average particle size of particles is defined as the particle size (median size, D50) at which the cumulative amount from the small diameter side reaches 50% in the volume-based particle size distribution measured by a laser diffraction / scattering method. The volume average particle size can be measured, for example, by using a laser diffraction / scattering type particle size measuring device for particles suspended in water.
[0033] The specific carbon material has a BET specific surface area based on nitrogen adsorption capacity of 0.5 m 2 / g~10m 2 It is preferable that the molecular weight is 1 / g. The BET specific surface area of a specific carbon material is 0.5m 2 / g or more, the input / output characteristics tend to improve, and 2 When the content is 1.0 to 1.0 μm, the initial charge / discharge efficiency tends to be improved. The BET specific surface area of a specific carbon material is 0.6 m 2 / g or more, 2 / g or more, and 2 The BET specific surface area of the specific carbon material may be 8 m 2 / g or less, and 2 / g or less, and 2 / g or less.
[0034] The BET specific surface area of a specific carbon material is calculated from the nitrogen adsorption capacity in accordance with JIS Z 8830:2013. For example, AUTOSORB-1 (product name) manufactured by QUANTACHROME can be used as an evaluation device. When measuring the BET specific surface area, a pretreatment is performed to remove moisture by heating, since it is believed that moisture adsorbed on the surface and inside of the measurement sample affects the gas adsorption capacity. After the pretreatment, the measurement is performed with the evaluation temperature set to 77K and the evaluation pressure range set to less than 1 in terms of relative pressure (equilibrium pressure with respect to the saturated vapor pressure). In the pretreatment, the measurement cell containing 0.05 g of the measurement sample is depressurized to less than 10 Pa using a vacuum pump. It is then heated to 110°C and held at 110°C for at least 3 hours. After that, it is naturally cooled to room temperature (25°C) while maintaining the depressurized state.
[0035] The mass ratio of the negative electrode active material to the solid electrolyte contained in the negative electrode (negative electrode active material:solid electrolyte) is preferably 5:95 to 70:30, more preferably 10:90 to 50:50, and further preferably 15:85 to 40:60.
[0036] The negative electrode active material may contain only the specific carbon material, or may contain a negative electrode active material other than the specific carbon material. As for the negative electrode active material other than the specific carbon material, the interplanar spacing (d 002) is 0.350 nm or more, carbon material with springback rate of less than 13%, Nb 2 O 5 , Li 4 Ti 5 O 12 , oxides such as SiO, metals or semi-metals such as In, Al, Si, and Sn, and the like.
[0037] When the negative electrode active material contains a specific carbon material and a negative electrode active material other than the specific carbon material, the proportion of the specific carbon material in the entire negative electrode active material is preferably 50 mass% or more, more preferably 70 mass% or more, and even more preferably 80 mass% or more. When the negative electrode active material contains a specific carbon material and a negative electrode active material other than the specific carbon material, the proportion of the specific carbon material may be 99 mass % or less, or may be 95 mass % or less, of the entire negative electrode active material.
[0038] The amount of the negative electrode active material contained in the negative electrode may be 10 mass % or more, 20 mass % or more, or 30 mass % or more of the total materials constituting the negative electrode (excluding the negative electrode current collector and volatile components). The amount of negative electrode active material contained in the negative electrode may be 95% by mass or less, 90% by mass or less, or 80% by mass or less of the total materials constituting the negative electrode (excluding the negative electrode current collector and volatile components).
[0039] (solid electrolyte) The type of solid electrolyte contained in the negative electrode is not particularly limited and can be selected from materials that can be used as electrolytes in all-solid-state batteries. Representative solid electrolytes include sulfide solid electrolytes, oxide solid electrolytes, and polymer solid electrolytes. From the viewpoint of achieving high input power, sulfide solid electrolytes and polymer solid electrolytes are preferred, and from the viewpoint of thermal stability, sulfide solid electrolytes are more preferred. The solid electrolyte may be used alone or in combination of two or more kinds.
[0040] The sulfide solid electrolyte may be a compound containing a metal element that becomes a conducting ion and sulfur (S). Examples of the metal element include Li, Na, K, Mg, and Ca. Among them, Li is preferable as the metal element. The sulfide solid electrolyte may contain Li and S, and at least one selected from the group consisting of P, Si, Ge, Al, and B. Among them, a sulfide solid electrolyte containing Li, S, and P (hereinafter also referred to as an LPS-type sulfide solid electrolyte) is preferable. From the viewpoint of ion conductivity, the sulfide solid electrolyte may contain a halogen element such as Cl, Br, or I. From the viewpoint of chemical stability, the sulfide solid electrolyte may contain oxygen (O).
[0041] Specifically, the LPS-type sulfide solid electrolyte is Li 2 SP 2 S 5 , Li 2 SP 2 S 5 - LiI, Li 2 SP 2 S 5 -Li 2 O, Li 2 SP 2 S 5 -Li 2 O-LiI, Li 2 S-SiS 2 , Li 2 S-SiS 2 - LiI, Li 2 S-SiS 2 -LiBr, Li 2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B 2 S 3 - LiI, Li 2 S-SiS 2 -P 2 S 5 - LiI, Li 2 S.B. 2 S 3 , LiI-Li 2 SP 2 O 5 , LiI-Li 3 PO 4 -P 2 S5 , LiBr-LiI-Li 2 SP 2 S 5 , Li 2 SP 2 S 5 -Z m S n (wherein m and n are positive numbers, and Z is Ge, Zn or Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS 2 -Li x MO y (wherein x and y are positive numbers, and M is P, Si, Ge, B, Al, Ga, or In).
[0042] In the above, "Li 2 SP 2 S 5 " means that Li is used as a raw material. 2 S and P 2 S 5 The same applies to other descriptions.
[0043] Among the LPS-type sulfide solid electrolytes, Li 2 S and P 2 S 5 A sulfide solid electrolyte obtained using the following formula is preferred, and a sulfide solid electrolyte satisfying the following formula is more preferred. Li 3+x+5y P 1-y S 4 (0 <x≦0.6、0<y≦0.2)
[0044] As an oxide solid electrolyte, NASICON (Na 3 Zr 2 PSi 2 O 12 Compounds having a NASICON type crystal structure have high ionic conductivity and are stable in the atmosphere. Compounds having a NASICON type crystal structure include phosphates containing lithium. Examples of phosphates include complex lithium phosphates with Ti (e.g., Li 1+x Al x Ti 2-x (PO 4 ) 3 ) and compounds in which all or a part of the Ti in the above-mentioned composite lithium phosphate is replaced with a tetravalent transition metal such as Ge, Sn, Hf, or Zr, or a trivalent transition metal such as Al, Ga, In, Y, or La. Specifically, compounds having a NASICON crystal structure include Li-Al-Ge-PO-based materials (Li 1+x Al x Ge 2-x (PO 4 ) 3 ), Li-Al-Zr-PO material (Li 1+x Al x Zr 2-x (PO 4 ) 3 ), Li-Al-Ti-PO material (Li 1+x Al x Ti 2-x (PO 4 ) 3 ) etc.
[0045] The polymer solid electrolyte may be a mixture (complex) of a polymer compound and an electrolyte salt. Specific examples of the polymer compound include polyether polymer compounds such as polyethylene oxide (PEO) and polypropylene oxide (PPO), polyamine polymer compounds such as polyethyleneimine (PEI), and polysulfide polymer compounds such as polyalkylene sulfide (PAS). Among these, polyether polymer compounds are preferred.
[0046] Specifically, the electrolyte salt is LiPF 6 , LiBF 4 , Li[FSI], Li[TFSI], Li[f3C], Li[BOB], LiClO 4 , LiBF 3 (CF 3), LiBF 3 (C 2 F 5 ), LiBF 3 (C 3 F 7 ), LiBF 3 (C 4 F 9 ), LiC(SO 2 CF 3 ) 3 , C.F. 3 SO 2 OLi, C.F. 3 Examples include lithium salts such as COOLi and RCOOLi (wherein R is an alkyl group, a phenyl group, or a naphthyl group having 1 to 4 carbon atoms). Among these, imide-based lithium salts such as Li[TFSI] and Li[FSI] are preferred.
[0047] In the above, [FSI] means bis(fluorosulfonyl)imide anion, [TFSI] means bis(trifluoromethanesulfonyl)imide anion, [BOB] means bis(oxalate borate) anion, and [f3C] means tris(fluorosulfonyl)carbanion.
[0048] The amount of the polymer compound in the mixture of the polymer compound and the electrolyte salt may be 1 mol or more, 5 mol or more, or 10 mol or more per mol of the electrolyte salt. The amount of the polymer compound in the mixture of the polymer compound and the electrolyte salt may be 50 mol or less, 40 mol or less, or 30 mol or less, per 1 mol of the electrolyte salt.
[0049] The polymer solid electrolyte may be a polymer compound having ion conductivity (hereinafter, also referred to as an ion-conducting polymer compound). The ion-conductive polymer compound may be in a state where a base polymer is doped with a dopant. Although the base polymer generally does not tend to exhibit ion conductivity, it is presumed that a pair of positive and negative charges is formed in the structure of the base polymer by doping the dopant and oxidizing or reducing the base polymer, thereby forming an ion-conductive path.
[0050] The base polymer is not particularly limited as long as it is a polymer that can be oxidized or reduced by a dopant.Specific examples of the base polymer include polyphenylene sulfide (PPS), poly(p-phenylene oxide) (PPO), polyether ether ketone (PEEK), polyphthalamide (PPA), polythiophene, polyaniline, polyacetylene, polythiazyl, polydiacetylene, polypyrrole, polyparaphenylene, polynaphthylene, and polyanthracene.
[0051] The dopant may be either an acceptor, which is an electron-accepting dopant, or a donor, which is an electron-donating dopant, i.e., the dopant may be either an oxidizing agent or a reducing agent.
[0052] Acceptors (oxidizing agents) include halogens such as bromine, iodine, and chlorine, as well as BF 3 , P.F. 5 , AsF 5 , SbF 5 Lewis acids such as HNO 3 , H 2 SO 4 , HClO 4 , HF, HCl, FSO 3 H, C.F. 3 SO 3 Protonic acids such as H, FeCl 3 , MoCl 5 , WCl 5 , SnCl 4 , MoF 5 , RuF 5 , TaBr 4 , TaBr 5 , SnI 4 Examples of the acceptor include transition metal halides such as those mentioned above, organic compounds such as 2,3-dichloro-5,6-dicyano-p-benzoquinone (DDQ), tetrachloro-1,4-benzoquinone (chloranil), tetracyanoquinodimethane (TCNQ), and tetracyanoethylene (TCNE), and oxygen. The acceptor may be used alone or in combination of two or more kinds.
[0053] Examples of the donor (reducing agent) include alkali metals such as Li, Na, K, Rb, Cs, etc., alkaline earth metals such as Be, Mg, Ca, etc., ammonium salts such as tetraethylammonium salts, tetrabutylammonium salts, etc., hydrogen, etc. The donor may be used alone or in combination of two or more kinds.
[0054] The mass ratio of the base polymer to the dopant (base polymer:dopant) is preferably 99:1 to 20:80, more preferably 95:5 to 30:70, and further preferably 90:10 to 50:50.
[0055] The method of doping the base polymer with the dopant includes a method of evaporating or sublimating the dopant and contacting the base polymer with the vapor. In this case, the base polymer may be formed into a sheet. The conditions for evaporating or sublimating the dopant can be set according to the properties of the dopant. The doping of the base polymer with the dopant may be performed by an electrochemical process.
[0056] The amount of solid electrolyte contained in the negative electrode may be 1 mass % or more, 5 mass % or more, or 10 mass % or more of the total materials constituting the negative electrode (excluding the negative electrode current collector and volatile components). The amount of solid electrolyte contained in the negative electrode may be 40 mass % or less, 30 mass % or less, or 20 mass % or less of the total materials constituting the negative electrode (excluding the negative electrode current collector and volatile components).
[0057] The solid electrolyte may be in the form of particles. In this case, the volume average particle diameter of the solid electrolyte is preferably 0.1 μm to 100 μm. If the volume average particle diameter of the solid electrolyte is 0.1 μm or more, it tends to be easily mixed with the carbon material, and if it is 100 μm or less, a sufficient battery capacity tends to be obtained. The volume average particle size of the solid electrolyte may be 0.2 μm or more, 0.4 μm or more, or 0.5 μm or more. The volume average particle size of the solid electrolyte may be 80 μm or less, 60 μm or less, or 50 μm or less.
[0058] The negative electrode may contain components other than the negative electrode active material and the solid electrolyte, as necessary, such as a conductive material and a binder.
[0059] Examples of the conductive material include carbon materials such as acetylene black, carbon black, and carbon fiber (excluding the above-mentioned negative electrode active material). The conductive material contained in the negative electrode material may be one type or two or more types.
[0060] The amount of the conductive material contained in the negative electrode may be 0.1 mass % or more, 0.3 mass % or more, or 0.5 mass % or more of the total materials constituting the negative electrode (excluding the negative electrode current collector and volatile components). The amount of conductive material contained in the negative electrode may be 5 mass % or less, 3 mass % or less, or 1 mass % or less of the total materials constituting the negative electrode (excluding the negative electrode current collector and volatile components).
[0061] Examples of the binder include polymers having monomers such as tetrafluoroethylene, acrylic acid, maleic acid, and ethyl methacrylate as polymerization components, styrene-butadiene rubber, isoprene rubber, and acrylic rubber.
[0062] When the negative electrode contains components other than the negative electrode active material and the solid electrolyte, the total amount of the negative electrode active material and the solid electrolyte may be 99.9 mass % or less, 99 mass % or less, or 97 mass % or less of the entire materials constituting the negative electrode (excluding the negative electrode current collector and volatile components). When the negative electrode contains components other than the negative electrode active material and the solid electrolyte, the total amount of the negative electrode active material and the solid electrolyte may be 85 mass % or more, 90 mass % or more, or 92 mass % or more of the entire materials constituting the negative electrode (excluding the negative electrode current collector and volatile components).
[0063] (Negative electrode current collector) The negative electrode may be one in which a layer containing the material constituting the negative electrode described above (hereinafter also referred to as negative electrode active material layer) is formed on a negative electrode current collector. The material of the negative electrode current collector is not particularly limited, but is preferably a conductive material containing copper (Cu). Examples of the conductive material containing copper include foils, plate-like materials, mesh-like materials, and the like, such as electrolytic copper foil, rolled copper foil, and copper alloy foil.
[0064] The thickness of the negative electrode active material layer formed on the negative electrode current collector is not particularly limited, and can be selected depending on the size, performance, etc. of the all-solid-state battery including the negative electrode. From the viewpoint of electrical conductivity, the thickness of the negative electrode active material layer may be 10 μm or more, 15 μm or more, or 20 μm or more. From the viewpoint of suppressing bias in charging and discharging caused by variations in the charge level of the negative electrode active material near the surface of the negative electrode, the thickness of the negative electrode active material layer may be 100 μm or less, 75 μm or less, or 50 μm or less.
[0065] <All-solid-state battery> The all-solid-state battery of the present disclosure includes the above-mentioned negative electrode, a positive electrode, and a solid electrolyte layer disposed between the negative electrode and the positive electrode.
[0066] FIG. 1 is a cross-sectional view illustrating a schematic example of the configuration of an all-solid-state battery. The all-solid-state battery 100 shown in FIG. 1 includes a negative electrode 16 including a negative electrode active material layer 12 and a negative electrode current collector 14, a positive electrode 17 including a positive electrode active material layer 13 and a positive electrode current collector 15, and a solid electrolyte layer 11 disposed between the positive electrode 16 and the negative electrode 17. In an embodiment, the negative electrode active material layer 12 includes a negative electrode active material and a solid electrolyte that is the same as the solid electrolyte contained in the solid electrolyte layer 11, and the positive electrode active material layer 13 includes a positive electrode active material and a solid electrolyte that is the same as the solid electrolyte contained in the solid electrolyte layer 11.
[0067] (positive electrode) The configuration of the positive electrode is not particularly limited and can be selected from those commonly used as positive electrodes for all-solid-state batteries. In one embodiment, the positive electrode includes a positive electrode active material and a solid electrolyte.
[0068] Examples of the positive electrode active material include lithium transition metal compounds such as lithium transition metal oxides and lithium transition metal phosphates. Examples of the lithium transition metal oxide include lithium manganate, lithium nickelate, lithium cobaltate, and lithium transition metal oxides in which a part of the transition metals contained in these lithium transition metal oxides, such as Mn, Ni, and Co, is replaced with one or more other transition metals, or metal elements (typical elements) such as Mg and Al. That is, the lithium transition metal oxide is LiM 1 O 2 Or LiM 1 2 O 4 (M 1 Li(Co) may be used as the lithium transition metal oxide. 1 / 3 Ni 1 / 3 Mn 1 / 3 )O 2 , LiNi 1 / 2 Mn 1 / 2 O 2 , LiNi 1 / 2 Mn 3 / 2 O 4 etc.
[0069] From the viewpoint of improving the energy density, the lithium transition metal oxide is preferably a compound represented by the following formula: Li a Ni b Co c M 2 d O 2+e In the formula, M 2 is at least one selected from the group consisting of Al, Mn, Mg, and Ca, and a, b, c, d, and e are numbers that satisfy 0.2≦a≦1.2, 0.5≦b≦0.9, 0.1≦c≦0.4, 0≦d≦0.2, and −0.2≦e≦0.2, respectively, and that satisfy b+c+d=1.
[0070] Specifically, the lithium transition metal phosphate is LiFePO 4 , LiMnPO4 , LiMn x M 3 1-x PO 4 (0.3≦x≦1, M 3 is at least one element selected from the group consisting of Fe, Ni, Co, Ti, Cu, Zn, Mg, and Zr).
[0071] The positive electrode may contain only one type of positive electrode active material, or two or more types.
[0072] The positive electrode active material is preferably in the form of particles. The particles may be ungranulated primary particles or granulated secondary particles. The volume average particle size of the positive electrode active material may be 0.1 μm or more, 1 μm or more, or 5 μm or more. The volume average particle size of the positive electrode active material may be 30 μm or less, 25 μm or less, or 20 μm or less.
[0073] The amount of positive electrode active material contained in the positive electrode may be 60 mass % or more, 65 mass % or more, or 70 mass % or more of the total materials constituting the positive electrode (excluding the positive electrode current collector and volatile components). The amount of positive electrode active material contained in the positive electrode may be 99% by mass or less, 95% by mass or less, or 90% by mass or less of the total materials constituting the positive electrode (excluding the positive electrode current collector and volatile components).
[0074] The solid electrolyte contained in the positive electrode may be the same as the solid electrolyte that may be contained in the negative electrode. The solid electrolyte contained in the positive electrode may be the same as or different from the solid electrolyte contained in the negative electrode, and is preferably the same.
[0075] The amount of solid electrolyte contained in the positive electrode may be 1 mass % or more, 5 mass % or more, or 10 mass % or more of the total materials constituting the positive electrode (excluding the positive electrode current collector and volatile components). The amount of solid electrolyte contained in the positive electrode may be 40 mass % or less, 30 mass % or less, or 20 mass % or less of the total materials constituting the positive electrode (excluding the positive electrode current collector and volatile components).
[0076] The positive electrode may contain components other than the positive electrode active material and the solid electrolyte as necessary. For example, it may contain a conductive material, a binder, etc. Examples of the conductive material and the binder include the conductive material and the binder that may be contained in the negative electrode described above.
[0077] When the positive electrode contains components other than the positive electrode active material and the solid electrolyte, the total amount of the positive electrode active material and the solid electrolyte may be 99.9 mass % or less, 99 mass % or less, or 97 mass % or less of the entire materials constituting the positive electrode (excluding the positive electrode current collector and volatile components). When the positive electrode contains components other than the positive electrode active material and the solid electrolyte, the total amount of the positive electrode active material and the solid electrolyte may be 85 mass % or more, 90 mass % or more, or 92 mass % or more of the entire materials constituting the positive electrode (excluding the positive electrode current collector and volatile components).
[0078] (Positive electrode current collector) The positive electrode may be one in which a layer containing the material constituting the positive electrode described above (hereinafter also referred to as a positive electrode active material layer) is formed on a positive electrode current collector. The type of the positive electrode current collector is not particularly limited, and examples thereof include foils, plates, meshes, etc., containing metals such as aluminum, stainless steel, and titanium, and carbon.
[0079] The thickness of the positive electrode active material layer formed on the positive electrode current collector is not particularly limited, and can be selected depending on the size, performance, etc. of the all-solid-state battery. From the viewpoint of electrical conductivity, the thickness of the positive electrode active material layer may be 10 μm or more, 15 μm or more, or 20 μm or more. From the viewpoint of reducing the volume of the positive electrode, the thickness of the positive electrode active material layer may be 100 μm or less, 75 μm or less, or 50 μm or less.
[0080] (Solid electrolyte layer) The solid electrolyte layer has a function of mediating the movement of ions between the positive electrode and the negative electrode, and also a function of providing electrical insulation between the positive electrode and the negative electrode. The solid electrolyte contained in the solid electrolyte layer may be the solid electrolyte that may be contained in the negative electrode and positive electrode described above. The solid electrolyte contained in the solid electrolyte layer may be the same as or different from the solid electrolytes contained in the negative electrode and positive electrode, and is preferably the same.
[0081] The amount of solid electrolyte contained in the solid electrolyte layer may be 30 mass % or more, 40 mass % or more, or 50 mass % or more of the total materials (excluding volatile components) constituting the solid electrolyte layer. The amount of solid electrolyte contained in the solid electrolyte layer may be 100 mass % or less, 99 mass % or less, or 95 mass % or less of the entire materials (excluding volatile components) constituting the solid electrolyte layer.
[0082] The solid electrolyte layer may contain components other than the solid electrolyte as necessary. For example, it may contain a binder. Examples of the binder include the binder that may be contained in the negative electrode described above.
[0083] The amount of components other than the solid electrolyte contained in the solid electrolyte layer may be 1 mass % or more, 3 mass % or more, or 5 mass % or more of the total materials (excluding volatile components) constituting the solid electrolyte layer. The amount of components other than the solid electrolyte contained in the solid electrolyte layer may be 50 mass % or less, 40 mass % or less, or 30 mass % or less of the entire materials (excluding volatile components) constituting the solid electrolyte layer.
[0084] The thickness of the solid electrolyte layer is not particularly limited and can be selected depending on the size, performance, etc. of the all-solid-state battery. From the viewpoint of improving the strength and safety of the all-solid-state battery, the thickness of the solid electrolyte layer may be 5 μm or more, 10 μm or more, or 15 μm or more. From the viewpoint of reducing the internal resistance and large current characteristics of the all-solid-state battery, the thickness of the solid electrolyte layer may be 200 μm or less, 150 μm or less, or 100 μm or less.
[0085] <Negative electrode active material for all-solid-state batteries> The negative electrode active material for an all-solid-state battery according to the present disclosure has a lattice spacing (d 002 ) is 0.336 nm or more and less than 0.350 nm and the springback rate is 13% or more.
[0086] An all-solid-state battery using the above-mentioned negative electrode active material has superior cycle characteristics compared to a conventional all-solid-state battery using a carbon material as the negative electrode active material. The negative electrode active material is used, for example, in the manufacture of the above-mentioned negative electrode and all-solid-state battery. The details and preferred aspects of the negative electrode active material are the same as those of the negative electrode active material contained in the negative electrode described above. EXAMPLES
[0087] The present disclosure will be described more specifically below with reference to examples, but the present disclosure is not limited to these examples.
[0088] <Production of all-solid-state batteries> Interplanar spacing (d 002 Carbon materials 1 to 8 serving as negative electrode active materials, each having a spring back rate and a hardness shown in Table 1, were mixed with a solid electrolyte in a mass ratio (carbon material:solid electrolyte) shown in Table 1.
[0089] As a solid electrolyte, Li 2 S (75 mol%) and P 2 S 5(25 mol%) of a sulfide solid electrolyte (shown as LPS in Table 1) and a polymer solid electrolyte (shown as PEO in Table 1) obtained from a mixture (complex) obtained by mixing polyethylene oxide and Li[FSI] as an electrolyte salt in a molar ratio (polyethylene oxide:electrolyte salt) of 20:1 were used.
[0090] The mixture obtained by mixing the carbon material and the solid electrolyte was weighed so that the amount of carbon material contained in the mixture was the amount calculated by the method described below, and pressure was applied to produce a disk-shaped pellet (thickness 3 mm, diameter 10 mm) with a relative density of 90% or more to be used as the negative electrode. A disk-shaped pellet (thickness 5 mm, diameter 10 mm) with a relative density of 95% or more was prepared using the same solid electrolyte as that used in the preparation of the negative electrode, and used as the solid electrolyte layer. The negative electrode, solid electrolyte layer, and lithium-indium alloy foil (counter electrode) attached to a Cu mesh were stacked in that order and placed in a CR2032-type coin cell container. The top of the battery container was crimped and sealed with an insulating gasket to prepare a coin-type half cell as an all-solid-state battery for evaluation.
[0091] Details of carbon materials 1 to 8 are shown below. Carbon material 1: Coke A, which had been granulated to have a volume average particle size of 20 μm, was placed in a graphite crucible, heated to 3000° C. in an inert atmosphere, and held at that state for 5 hours to prepare a sample, which was designated as carbon material 1. Carbon material 2: Coke B, which had been granulated to have a volume average particle size of 16 μm, was loaded into a graphite crucible, and the temperature was raised to 1000° C. in an inert atmosphere and held at that state for 5 hours to prepare a sample, which was designated as carbon material 2. Carbon material 3: Coke B, which had been granulated to have a volume average particle size of 9 μm, was placed in a graphite crucible, heated to 3000° C. in an inert atmosphere, and held for 5 hours to prepare a sample, which was designated as carbon material 3. Carbon material 4: Coke B, which had been granulated to have a volume average particle size of 16 μm, was filled into a graphite crucible and heated to 1000° C. in an inert atmosphere and held for 5 hours. After that, the mixture was further classified to remove fine powder, and a sample was prepared. This sample was designated as carbon material 4. Carbon material 5: Coke C, which had been granulated to have a volume average particle size of 15 μm, and petroleum pitch were mixed in a mass ratio of 97:3 (coke C: petroleum pitch) and formed into a block. The mixture was then loaded into a graphite crucible and heated to 3000°C in an inert atmosphere, held for 5 hours, and cooled. The cooled block was broken up by hand and sieved to prepare a sample. This sample was designated carbon material 5. Carbon material 6: Coke B crushed to have a volume average particle size of 12 μm and 20 μm was mixed in a mass ratio of 50:50 (12 μm:20 μm). The mixture was then filled into a graphite crucible and heated to 1000°C in an inert atmosphere for 5 hours to prepare a sample. This sample was designated carbon material 6. Carbon material 7: Coke B, which had been granulated to a volume average particle size of 23 μm, and petroleum pitch were mixed in a mass ratio of 90:10 (coke B: petroleum pitch) and molded into a block. The mixture was then loaded into a graphite crucible, heated to 3000°C in an inert atmosphere, held for 5 hours, and cooled. The cooled block was crushed and sieved to obtain a powder. This powder and petroleum pitch were mixed in a mass ratio of 90:10 (powder: petroleum pitch). This mixture was loaded into a graphite crucible, heated to 1000°C in an inert atmosphere, and held for 5 hours to prepare a sample. This sample was designated carbon material 7. Carbon material 8: Coke A sized to have a volume average particle size of 16 μm was used as carbon material 8.
[0092] Details of cokes A to C are shown below. Coke A: Petroleum coke with a volume average particle size of 18 μm Coke B: Coal-based coke with a volume average particle size of 14 μm Coke C: Petroleum coke with a volume average particle size of 7 μm
[0093] <How to calculate the amount of carbon material in a mixture> (1) Carboxymethyl cellulose (CMC) as a thickener and styrene butadiene rubber (SBR) as a binder were added to the carbon material used in the examples and comparative examples. The mass ratio of these was carbon material:CMC:SBR=98:1:1. Purified water as a dispersion solvent was added to this and kneaded to prepare a slurry. A predetermined amount (5 mg / cm2) of this slurry was applied substantially evenly and homogeneously to both sides of a rolled copper foil with a thickness of 10 μm, which was a current collector for the negative electrode. 2 The density of the negative electrode active material layer of the negative electrode plate was 1.3 g / cm 3 It was decided.
[0094] (2) A coin-type battery was prepared by sandwiching a 30 μm-thick single-layer polyethylene separator (product name: Hipore, manufactured by Asahi Kasei Corporation, "Hipore" is a registered trademark) between a negative electrode plate (mass of carbon material: 7.54 mg) punched into a circle with a diameter of 14 mm and a Li metal plate punched into a circle with a diameter of 15 mm. The non-aqueous electrolyte for the coin-type battery is a mixed solvent of cyclic carbonate ethylene carbonate (EC), chain carbonate dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) in a volume ratio of 2:3:2, and lithium hexafluorophosphate (LiPF 6 ) was dissolved at a concentration of 1.2 mol / L, and vinylene carbonate (VC) was added at a concentration of 1.0 mass %.
[0095] (3) The coin-type battery was charged at a constant current of 0.2 CA to 0 V (vs. Li / Li+) in a 25°C environment, and then charged at a constant voltage of 0.01 CA from the point where 0 V (vs. Li / Li+) was reached (initial charge). It was then discharged at a constant current of 0.2 CA to 1.5 V (initial discharge), and the initial discharge capacity (mAh) was measured. A 30-minute break was taken between charge and discharge.
[0096] (4) From the measured initial discharge capacity (YmAh) and the mass of the carbon material contained in the negative electrode plate (7.54mg), the mass of the carbon material (Xmg) when the discharge capacity of the coin battery (designed battery capacity) becomes 0.3mAh was calculated using the following formula. The calculated mass of the carbon material was regarded as the mass of the carbon material in the mixture used to prepare the all-solid-state battery. X(mg)=(7.54(mg)×0.3(mAh)) / Y(mAh)
[0097] <Capacity evaluation of all-solid-state batteries> As an index for determining whether or not an all-solid-state battery operates as designed, the ratio of the initial discharge capacity to the battery design capacity was calculated as follows. In an environment of 25°C, the all-solid-state battery was charged at a constant current to -0.57V (vs. Li / In) at a current value equivalent to 0.05CA. The all-solid-state battery was then charged at a constant voltage until the current value attenuated to a current value equivalent to 0.005CA. The capacity at this time was taken as the initial charge capacity (mAh). After leaving the battery in this state for 30 minutes, the all-solid-state battery was discharged at a constant current to 1.0V (vs. Li / In) at a current value equivalent to 0.05CA. The capacity at this time was taken as the initial discharge capacity (mAh) of the all-solid-state battery.
[0098] The capacity evaluation (%) was calculated from the initial discharge capacity of the obtained all-solid-state battery and the battery design capacity (0.3 mAh) according to the following formula. The results are shown in Table 1. Capacity evaluation (%) = (initial discharge capacity of all-solid-state battery / battery design capacity) × 100
[0099] <Measurement of capacity retention rate and initial charge / discharge efficiency of all-solid-state batteries> The all-solid-state battery was repeatedly charged and discharged 10 times under the same conditions as those for measuring the initial discharge capacity, and the 10th discharge capacity was measured. From the obtained values, the capacity retention rate (%) and the initial charge / discharge efficiency (%) were calculated using the following formula. The results are shown in Table 1. Capacity retention rate (%) = (10th discharge capacity (mAh) / initial discharge capacity (mAh)) x 100 Initial charge / discharge efficiency (%) = (initial discharge capacity (mAh) / initial charge capacity (mAh)) x 100
[0100] [Table 1]
[0101] As shown in Table 1, the interplanar spacing (d 002 The all-solid-state batteries of the examples using a carbon material having a surface roughness of 0.336 nm or more and less than 0.350 nm and a springback rate of 13% or more as a negative electrode active material exhibited good capacity evaluation and capacity retention rate, and also had excellent initial charge / discharge efficiency. The interplanar spacing (d 002 ) is 0.336 nm or more and less than 0.350 nm, but the all-solid-state battery of Comparative Example 1 using a carbon material having a springback rate of less than 13% as the negative electrode active material is inferior in capacity evaluation and capacity retention rate to the examples. The springback rate is 13% or more, but the interplanar spacing (d 002 The all-solid-state battery of Comparative Example 2, which used a carbon material having a diameter of 0.350 nm as the negative electrode active material, had an initial charge-discharge efficiency inferior to that of the Examples.
[0102] The disclosure of Japanese Patent Application No. 2020-215777 is incorporated herein by reference in its entirety. All publications, patent applications, and standards mentioned in this specification are incorporated by reference into this specification to the same extent as if each individual publication, patent application, and standard was specifically and individually indicated to be incorporated by reference.
Claims
1. The negative electrode active material includes a solid electrolyte, and the negative electrode active material has a lattice spacing (d 002 ) is 0.336 nm or more and less than 0.350 nm and a springback rate of 13% or more, wherein the springback rate is measured by the following method. A cylindrical powder molding die (diameter 15.0 mm) is filled with 3.000 (±0.005) g of carbon material. The carbon material filled in the die is measured using an autograph to determine that the density of the carbon material is 1.65 g / cm 3 The carbon material is pressed uniaxially until the density of the carbon material reaches 1.65 g / cm 3 After the pressure reaches 2N, the pressure is released to 0N and the state (0N state) is maintained for 30 seconds. After the 30 second hold, the sample is pressurized using an autograph, and the density ρ of the sample when the pressure reaches 2N is measured. after (g / cm 3 ) is measured. The springback rate is calculated from the obtained value by the following formula. Springback rate (%) = {(1.65 - ρ after ) / 1.65} × 100
2. The negative electrode for an all-solid-state battery according to claim 1, wherein the carbon material is particles having a volume average particle diameter of 5 μm to 30 μm.
3. The BET specific surface area based on the nitrogen adsorption capacity of the carbon material is 0.5 m 2 / g to 10m 2 The negative electrode for an all-solid-state battery according to claim 1 or 2, wherein the anode is a Cr-type Cr-type polymer.
4. The negative electrode for an all-solid-state battery according to any one of claims 1 to 3, wherein a mass ratio of the negative electrode active material to the solid electrolyte (negative electrode active material:solid electrolyte) is 5:95 to 70:
30.
5. The negative electrode for an all-solid-state battery according to any one of claims 1 to 4, wherein the solid electrolyte is a sulfide solid electrolyte.
6. 6. An all-solid-state battery comprising: the negative electrode for an all-solid-state battery according to claim 1; a positive electrode; and a solid electrolyte layer disposed between the negative electrode for an all-solid-state battery and the positive electrode.
7. A negative electrode active material for an all-solid-state battery for use in an electrode comprising a negative electrode active material and a solid electrolyte, the negative electrode active material having a lattice spacing (d 002 ) is 0.336 nm or more and less than 0.350 nm and has a springback rate of 13% or more, wherein the springback rate is measured by the following method. A cylindrical powder molding die (diameter 15.0 mm) is filled with 3.000 (±0.005) g of carbon material. The carbon material filled in the die is measured using an autograph to determine that the density of the carbon material is 1.65 g / cm 3 The carbon material is pressed uniaxially until the density of the carbon material reaches 1.65 g / cm 3 After the pressure reaches 2N, the pressure is released to 0N and the state (0N state) is maintained for 30 seconds. After the 30 second hold, the sample is pressurized using an autograph, and the density ρ of the sample when the pressure reaches 2N is measured. after (g / cm 3 ) is measured. The springback rate is calculated from the obtained value by the following formula. Springback rate (%) = {(1.65 - ρ after ) / 1.65} × 100
Citation Information
Patent Citations
All-solid battery
JP2011134617A
Negative electrode material for lithium ion secondary battery, negative electrode for lithium ion secondary battery, and lithium ion secondary battery
JP2014229517A
Carbonaceous material and method of using same
JP2019508355A
Compositions and uses thereof
JP2019532469A
All-solid secondary battery
JP2021136239A